Correlation Between Mental Health Literacy and Mental Health Status among Health Students - Nurdin, Andi Ardiansyah; Septialti, Delita (Universitas Ahmad Dahlan, 2025)
Mental health constitutes a fundamental and essential component of overall well-being. Particular attention must be given to mental health concerns, especially among vulnerable adolescent populations. Epidemiological data indicate a cyclical rise in the prevalence of mental health problem, which may be mitigated through improved mental health literacy. This study aims to examine the relationship between mental health literacy and mental health status among health students. A cross-sectional survey was conducted involving 380 health students from three health polytechnic institutions. Instruments included the SRQ-20 and the Mental Health Literacy Questionnaire (MHLq-SVa). The findings indicate a statistically significant association between mental health literacy levels and reported symptoms of mental-emotional disorders (p = 0.025). These results underscore the importance of integrating mental health literacy into the health education curriculum to promote early recognition and appropriate help-seeking behaviors.